Associations of lifestyle with mental health and well-being in Chinese adults: a nationwide study - Wang, Xue; Wu, Yibo; Shi, Xinji; Chen, Yu; Xu, Yahong; Xu, Hongbo; Ma, Yanan; Zang, Shuang (Frontiers in Nutrition, 2023)
Background: A healthy lifestyle is beneficial to individuals’ health. However, little is known about the associations of lifestyle factors with mental health and well-being. This study examined the associations of lifestyle factors with mental health (i.e., depression, anxiety, loneliness, perceived pressure, and self-rated health status) and well-being in Chinese adults. Methods: A nationally representative survey was conducted in China from 20 June 2022 to 31 August 2022. Data from the survey were analyzed using multiple linear regression to determine the associations of lifestyle with mental health and well-being in Chinese adults. Standardized regression coefficients (β) and 95% confidence intervals (CIs) were estimated using multiple linear regression. Results: The survey included 28138 Chinese adults. Multiple linear regression results showed that there were significant negative associations of lifestyle scores with scores of depression (β = -0.93, 95% CI: -0.98, -0.88), anxiety (β = -0.71, 95% CI: -0.76, -0.67), loneliness (β = -0.23, 95% CI: -0.24, -0.21), and perceived pressure (β = -0.19, 95% CI: -0.22, -0.16). Moreover, there were significant positive associations of lifestyle with self-rated health status (β = 1.99, 95% CI: 1.79, 2.20) and well-being (β = 0.96, 95% CI: 0.91, 1.02). Conclusions: This study provides insight into the associations of lifestyle factors with mental health and well-being and highlights the importance of improving and maintaining healthy lifestyle behaviors for favorable mental health and well-being.